PENGARUH PEMBERIAN PUPUK ORGANIK CAIR LIMBAH UDANG DAN BIOCHAR TEMPURUNG KELAPA TERHADAP KETERSEDIAAN N, P, DAN K TANAH PADA PERTUMBUHAN PAKCOY (Brassica rapa L.) - Putri, Jovanka Fitriani Adinda; Herlambang, Susila (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Soil types such as Entisol have low nutrient availability and water-holding capacity. Shrimp waste organic fertilizer and coconut shell biochar can be used to improve the physical and chemical properties of Entisol soil. The purpose of this research was to determine the effect of shrimp waste liquid organic fertilizer and coconut shell biochar on the availability of N, P, and K in the soil for the growth of Pakcoy. The research used a Completely Randomized Design (CRD) with two factors. The first factor was the concentration of shrimp waste liquid organic fertilizer consisting of P0 = 0 mL/L, P1 = 25 mL/L, P2 = 50 mL/L and P3 = 75 mL/L. The second factor was the dosage of coconut shell biochar consisting of B0 = 0 ton/ha, B1 = 10 ton/ha, B2 = 15 ton/ha and B3 = 20 ton/ha. The preliminary analysis parameters consisted of pH H2O, C-organic, N-available, P-available, K-available, N-total, P-total, K-total, and CEC. The research results were analyzed by using Analysis of Variance (ANOVA), and to determine the differences between treatments, a 5% DMRT (Duncan Multiple Range Test) was conducted. The research results indicate that the use of liquid organic fertilizer from shrimp waste with a concentration of 50 mL/L and a dose of coconut shell biochar at 20 tons/ha can increase the organic carbon content in the soil from 0.03% to 0.05%. A concentration of 75 mL/L for liquid organic fertilizer from shrimp waste and a dose of 20 tons/ha for coconut shell biochar can increase the available nitrogen content in the soil from 16.24 ppm to 40.67 ppm. There is no interaction with the height, number of leaves, anda root length of Pakcoy plants.